Physical activity and body composition among college students of physical culture, sport and recreation (2015)
Introduction: Physical activity is an important determinant of health-related lifestyle and its regular practice is associated with reduction of chronic diseases. Objectives: To describe the amount of physical activity in different domains (occupational, displacement and free time), and assess the Body Mass Index and body fat percentage of students. Methodology: An analytic, cross-sectional study was carried out in college students of a faculty of physical culture, sport and recreation. Physical activity was determined by Global Physical Activity Questionnaire. Physical activity in the occupational, displacement and free time domains, was assessed. Results: The prevalence of overweight was 21.0% and of obesity 3.6% according to body mass index. 12.6% had excess total body fat. 98.8% of students were physically active and comply with the recommendations of the World Health Organization on physical activity for health. Stratified analysis of excess weight, physical activity and sedentary behavior by semester, evidenced higher percentage overweight or obesity in sixth to tenth semester students than those from first to fifth semester. Conclusions: Most students analyzed were physically active. Students who were enrolled in the second half of the race had higher percentages of excess weight. To assess the level of physical activity in students of physical culture is important because they represent a group of future professionals focused on promoting healthy lifestyles related to adequate levels of physical activity.